Structural quality and load-bearing capacity of an Ultisol (Argissolo Vermelho amarelo) in mechanized coffee areas with different deployment times - Barbosa Sandoval, Fabio Henrique; Souza, Zigomar Menezes de; Lima, Elizeu de Souza; Silva, Reginaldo Barboza da [UNESP]; Oliveira, Ingrid Nehmi de; Aguilera Esteban, Diego Alexander; Lovera, Lenon Henrique (Soc Brasileira De Ciencia Do Solo, 2020)
The mechanized management systems used in Brazilian coffee plantations generate heavy machine traffic and lead to the application of loads on the soil that affect the soil structure and lead to widespread compaction. This study aimed to evaluate the influence of mechanized operations on coffee plantations with different deployment times on the soil structural quality of an Ultisol, based on its soil physical properties and soil load-bearing capacity. The experiment was carried out in Muzambinho, Sao Paulo State, Southeast Brazil, in coffee plantations (Coffee arabica L.) with 3, 16, and 32 years of service. In each area, corresponding to the coffee plantation's establishment period, soil samples were collected in the planting row (R), under the coffee canopy (UCC), and inter-row center (IRC) at the layers of 0.00-0.10, 0.10-0.20, and 0.20-0.40 m to evaluate soil penetration resistance, bulk density, porosity, wet aggregate stability, and preconsolidation pressure, to model soil load-bearing capacity. The deployment time of the coffee crop was a decisive factor in reducing the deterioration of the soil structure in the row, which was confirmed by better structural quality in the plantations with 16 and 32 years of establishment. Irrespective of crop deployment time, the effects of intensive machinery traffic on the coffee crop in the middle between the rows and in the area under the canopy are similar, resulting in high soil compaction, reflected in soil penetration resistance, soil bulk density, macroporosity, and load-bearing capacity. The longer the deployment time of the coffee cultivation areas (32 and 16 years), the higher the stability of the soil aggregates, and the larger the mean aggregate size.
Keywords: machinery traffic; preconsolidation pressure; soil properties; uniaxial compression; soil compaction